Luteolin ameliorates lipopolysaccharide-induced microcirculatory disturbance through inhibiting leukocyte adhesion in rat mesenteric venules - Jie Su; Han-Ting Xu; Jing-Jing Yu; Mei-Qiu Yan; Ting Wang; Ya-Jun Wu; Bo Li; Wen-Jie Lu; Chuan Wang; Shan-Shan Lei; Si-Min Chen; Su-Hong Chen; et al. (BMC, 2021)
Abstract Background Microcirculatory disturbance is closely associated with multiple diseases such as ischemic and septic stroke. Luteolin (3,4,5,7-tetrahydroxyflavone) is a vascular protective flavonoid present in several dietary foods. However, how luteolin plays a role in microcirculatory disturbance is still unknown. The purpose of this study was to find out the influence of luteolin on the lipopolysaccharide (LPS)-induced microcirculatory disturbance, focusing on its effect on leukocyte adhesion and the underlying mechanism of this effect. Methods After injecting LPS into rats, we used an inverted intravital microscope to observe the velocity of red blood cells in venules, numbers of leukocytes adherent to and emigrated across the venular wall, hydrogen peroxide production in venular walls and mast cell degranulation. Intestinal microcirculation blood flow was measured by High-resolution Laser Doppler Perfusion Imaging. Histological changes of small intestine and mesenteric arteries were evaluated. Additionally, cell adhesion stimulated by LPS was tested on EA.hy926 and THP-1 cells. The production of pro-inflammatory cytokines, adhesion molecules and the activation of TLR4/Myd88/NF-κB signaling pathway were determined. Results The results showed luteolin significantly inhibited LPS-induced leukocyte adhesion, hydrogen peroxide production and mast cell degranulation, and increased intestinal microcirculation blood flow and ameliorated pathological changes in the mesenteric artery and the small intestine. Furthermore, luteolin inhibited the release of pro-inflammatory cytokines, the expression of TLR4, Myd88, ICAM-1, and VCAM-1, the phosphorylation of IκB-α and NF-κB/p65 in LPS stimulated EA.hy926. Conclusions Our findings revealed that it is likely that luteolin can ameliorate microcirculatory disturbance. The inhibitory effects of luteolin on the leukocyte adhesion stimulated by LPS, which participates in the development of microcirculatory disturbance, are mediated through the regulation of the TLR4/Myd88/NF-κB signaling pathway.